2019
DOI: 10.1111/joop.12256
|View full text |Cite
|
Sign up to set email alerts
|

Testing cross‐lagged relationships between work‐related rumination and well‐being at work in a three‐wave longitudinal study across 1 and 2 years

Abstract: The aim of this three‐wave longitudinal study conducted among 664 Finnish employees was to examine the cross‐lagged relationships between various work‐related ruminative thoughts (affective rumination, problem‐solving pondering, lack of detachment from work) during off‐job time and employee well‐being (exhaustion, vigour). We tested normal, reversed, and reciprocal temporal relationships across 1 and 2 years using structural equation modelling. The analyses lent most support to the reversed temporal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 67 publications
7
55
0
Order By: Relevance
“…In a longitudinal panel study, Vahle-Hinz et al [22] provided evidence that while affective rumination predicted lower levels of recovery and did not affect creativity six months later, problem-solving pondering predicted higher levels of creativity but did not impair recovery status. Applying latent profile analysis, Kinnunen and colleagues [23,24] found that different configurations of affective rumination, problem-solving pondering, and (lack of) detachment differentially predicted changes in exhaustion, work engagement, and sleep problems. Finally, another longitudinal study by Firoozabadi and colleagues [25] applied growth curve modeling and found that while affective rumination predicted increases in exhaustion over twelve months, problem-solving pondering was only related to the initial level of exhaustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longitudinal panel study, Vahle-Hinz et al [22] provided evidence that while affective rumination predicted lower levels of recovery and did not affect creativity six months later, problem-solving pondering predicted higher levels of creativity but did not impair recovery status. Applying latent profile analysis, Kinnunen and colleagues [23,24] found that different configurations of affective rumination, problem-solving pondering, and (lack of) detachment differentially predicted changes in exhaustion, work engagement, and sleep problems. Finally, another longitudinal study by Firoozabadi and colleagues [25] applied growth curve modeling and found that while affective rumination predicted increases in exhaustion over twelve months, problem-solving pondering was only related to the initial level of exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…While the studies cited above have consistently shown the differential effects of affective rumination vs. problem-solving pondering, very few studies have investigated affective rumination and problem-solving pondering in concert with psychological detachment for exceptions see [8,23,24,26]. In this sense, although much of the above cited research explicitly refers to detachment, we run the risk of disconnecting research on affective rumination and problem-solving pondering from the large body of research on detachment.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that affective rumination is positively related to negative behavior, and problem-solving pondering is negatively related or Psychological Reports, in press 11 not related to negative behavior. Research specific to the field of work has also found that only affective rumination predicted poor job role performance (Kinnunen et al, 2017;Kinnunen et al, 2019). In view of this, it can be inferred that after affective rumination, employees may show counterproductive behaviors (e.g., show up late, leave early, etc.)…”
Section: Wrr and Counterproductive Behaviormentioning
confidence: 99%
“…The reason for this may relate to reduced self-regulatory capacity that would be needed to refrain from thinking about workrelated matters when it is not necessary (Sonnentag and Fritz, 2015). This reverse relationship has been shown in longitudinal studies lasting from four weeks (Sonnentag, Arbeus, Mahn, and Fritz, 2014) to two years (Kinnunen, Feldt, and de Bloom, 2019). In the future, either shortterm diary studies or long-term longitudinal studies are needed to better reveal causal relationships between break recovery and various recovery outcomes.…”
Section: Limitations and Suggestions For Future Studiesmentioning
confidence: 99%